ENHANCING SPIRITUAL COGNITION: BRUNEIAN MUSLIMS’ HOLISTIC ENGAGEMENT WITH QIRAAT PROFILES OF SURAH AL-FATIHAH AND YASIN - Abdelgelil, Mohamed Fathy Mohamed; Syed Bidin, Sharifah Norshah Bani; Japar, Aleya Fatehah; Husain, Muhammad Zakir; Lazim, Khairun Naqibah (Institut Agama Islam Negeri Bone, 2025)
This study examines the perceptions and attitudes of the Muslim community in Brunei Darussalam regarding the official development of the 10 Qirā’āt profile for the foundational Qur'anic chapters, Surah Al-Fatihah and Surah Yasin. These two Surahs are central to daily Muslim devotion, necessitating an understanding of the legal status (Hukm) and standardization of their authenticated recitation variations ('Ilm Qirā’āt). Employing a quantitative research design, data were collected using a questionnaire administered to 69 respondents to assess their levels of awareness, knowledge, interest, and views towards this profiling initiative. The findings indicate a significant dichotomy: while respondents generally exhibit a moderate level of knowledge regarding the specific variations within 'Ilm Qirā’āt, they overwhelmingly express a strong interest and positive attitude towards the Qirā’āt profiling effort. A substantial majority of the community supports the dissemination and formal introduction of the profile across various platforms, specifically highlighting mass media channels for wider reach. The implications suggest a clear mandate for structured, collaborative action. Religious authorities, educational institutions, and media entities must systematically coordinate promotional and educational programs to bridge the existing knowledge gap. Such efforts are crucial not only for preserving the authoritative knowledge of the Qirā’āt tradition but also for ensuring its accurate practice, thereby strengthening the Bruneian Muslim community's comprehensive appreciation of the Holy Qur'an.